...Or We Will Do Without the Theatre. Challenging the Urban Space, Drafting a New City Map Through Performances. (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
The article discusses the evolution of urban mapping and innovative urban design. It explores the transition from functional urban planning to more creative approaches inspired by artists such as Guy Debord, Yoko Ono and others. It suggests that the city is a stage for events, similar to Antonin Artaud’s vision. The central question is how the city can be transformed into a theatre through practical design rules. The paper presents two experiments. The first involves random map rearrangement, encouraging new exploration of familiar neighbourhoods. The second experiment introduces guidance and unpredictability, reflecting the uncertainties of architectural projects. These experiments aim to apply theatrical concepts to urban design. The article seeks to develop a manual for dramatic urban navigation, highlighting the inherent dramatic structure of the city and promoting innovative design regulations.
Keywords: Urban; Maps; Flânerie; Theatre; Performance